Defensive strategies of ROS in Programmed Cell Death associated with hypertensive response in plant pathogenesis - Nivedita Dey; Utpal Krishna Roy; Manashi Aditya; Soumen Bhattacharjee (Annals of Systems Biology - Peertechz Publications, 2020)
One of the important initial events upon recognition of a plant pathogen is the changes in the redox status of the infected cells due to the accumulation of Reactive Oxygen Species (ROS). Though plants have evolved an array of defensive strategies to resist stresses, including those from attack by pathogens, but the changed redox cue of the infected cells are often exploited by the plant for specific purpose as well. It is becoming evident gradually that ROS or the redox cue, which are generated during pathogen attack are recognized by plant as a signaling agent for triggering responses. The necrosis of infected tissue caused by ROS during pathogen infection increases host susceptibility to necrotrophic pathogen, but exhibit resistance to biotrophic pathogen. Evidences further support the view that ROS serve as a 'second messenger' in a systemic signaling network in plant defence leading to the expression of specific genes that trigger hypersensitive Response (HR). Avirulent pathogens often induce a biphasic ROS accumulation with a weak transient first phase, followed by a more intense continuous phase. A range of enzyme systems like respiratory burst oxidase homolog (Rboh or NADPH oxidase), Superoxide Dismutase (SOD) have been implicated in ROS turnover following pathogen recognition. In this review we provide the relevant findings of signaling role of ROS in plant defence responses. Special attention is given to the role of ROS in Programmed Cell Death (PCD) associated with HR during pathogenesis in plants.